Towards Resilient MSMEs: The Role of Organizational Resilience and Entrepreneurial Resilience - Roymon Panjaitan (Jurnal Manajemen dan Keuangan, 2022)
Resilient MSMEs can be influenced by strong entrepreneurial resilience and organizational resilience in facing the challenges of business competition dynamics. This study discussion aims to analyze the success of the seller's intelligent proactive ability in bridging entrepreneurial resilience and organizational resilience in resilient MSMEs, as well as the effect of moderation of environmental turbulence from the relationship of the smart proactive ability of sellers to resilient MSMEs. A total of 186 respondents were sampled to MSME businesses, data collection techniques in the form of questionnaires and interviews. SEM-PLS compound path analysis is used in this research, where the seller's intelligent proactive ability is used as mediation and environmental turbulence as a moderation function. The results of this study there is a positive correlation between entrepreneurial and organizational resilience to the proactive ability of smart sellers, positive relationships of the smart ability of sellers on resilient MSMEs, and the positive impact of the direct influence of entrepreneurial resilience to Tangguh MSMEs. However, there is a negative relationship of moderation of environmental turbulence as well as organizational resilience relationships in resilient MSMEs. The conceptual contribution of this study model provides positive stimulus in measuring resilience for MSMEs obtained from internal factors and external disturbances.